COTYLEDON MEASURE INFLUENCE TO GROWTH OF ULIN (Eusyderoxylon zwageri T. Et B.) SEEDLING - Lukman Hakim; Mohamad Anis Fauzi (Center for Forest Biotechnology and Tree Improvement (CFBTI), 2008)
Ulin (Eusideroxylon zwageri) has much bigger seed compared to others tree species. This condition poses some difficulties in seed collecting and seed transporting from seed collecting area to nursery. The aim of this research is to examine the correlation between Ulin seed length with stem and root length in nursery. The study used 4 provenances and 15 seeds per provenance. Regresion analyzes showed that seed length variable (X) versus stem length (Y1) has formula Y1= 9,601 + 0,446 X and seed length variable (X) versus root length (Y2) has formula Y1= 5,884 + 0,428 X. From both formula showed that seed length variable (X) are not significant to stemp length and root length variable.